Transcriptome analysis of reproductive tissue differentiation in Jatropha curcas Linn. - Govender, Nisha (Genom Data, 2017)
Shoot and inflorescence are central physiological and developmental tissues of plants. Flowering is one of the most important agronomic traits for improvement of crop yield. To analyze the vegetative to reproductive tissue transition in Jatropha curcas, gene expression profiles were generated from shoot and inflorescence tissues. RNA isolated from both tissues was sequenced using the Ilumina HiSeq 2500 platform. Differential gene expression analysis identified key biological processes associated with vegetative to reproductive tissue transition. The present data for J. curcas may inform the design of breeding strategies particularly with respect to reproductive tissue transition. The raw data of this study has been deposited in the NCBI's Sequence Read Archive (SRA) database with the accession number SRP090662.